Physical activity and sedentary behavior among ambulatory children with cerebral palsy using accelerometer: a cross-sectional study - Alamoudi, Njoud Aydhah; Algabbani, Maha F.; Al-Heizan, Muhammad O.; Alhusaini, Adel A. (Frontiers in Pediatrics, 2024)
Background and objective: Physical activity (PA) is paramount for childhood development and growth. However, children diagnosed with Cerebral Palsy (CP) were often considered sedentary, and their physical inactivity was associated with adverse health conditions and complications. Therefore, this study aimed to objectively describe and compare the PA levels and SB levels of children with and without CP of the same age group. It also studied the factors correlating with PA, SB, and step count per day in children with CP. Subjects and Methods: A cross-sectional study using a wristworn accelerometer was conducted. PA and SB were measured over seven consecutive days. Results: Eighty-five children aged 6-12 years, consisting of 41 children with CP and 44 TD children, participated in this study with a mean age of 9.18±1.95 and 8.45±1.78 years, respectively. According to the gross functional measures, 53.6% of children with CP were classified as first classification. A significant amount of time was spent in SB and Light PA (LPA) by children with CP compared to TD children, and no significant differences were observed in moderate PA (MPA) or step count. Gender mainly affected MPA as girls spent more time in MPA than boys. The age, height, and weight of children with CP correlate significantly with SB. As children's age, height, and weight increase, SB increases. Additionally, children with higher weights have lower step counts per day.This study showed that children with CP spend more time in LPA and SB than typically developed children. Therefore, concerted efforts are needed to encourage physical activity and reduce the sedentary lifestyle, to take into account the gender and anthropometric measures of children to enhance the quality of life among children with CP, and to consider gender and anthropometric measures of the children..